Realization of vOLT and development trend - Fengchao FU; Peng WANG; Yu MAO; Yongmei HUANG; Xiaobing GAO; Aihua ZHANG; Guoqiang LIN (Dianxin kexue)
SDN technology,NFV technology and cloud computing technology have been studied widely recently.How to realize vOLT based on these three techniques mentioned above was studied in order to solve theproblems that the OLTs of traditional PON faced,such as the OLTs of the PON were too difficultto operate and maintain,the resources allocation including ports,VLAN,MAC and others were not flexible,and theservice provisioning process was complicated.Four vOLT schemes were proposed.From the perspectiveof telecom operators,these four methods were compared and analyzed from the perspectives of application scenariosand the difficulty of introduction.Finally,the evolution route and the development trend of vOLT were conclued.